Atypical ovarian cycle length in dairy cows: Occurrence and effects on productivity and carbon emissions - Algherair, Ibrahim (2023)
Enteric fermentation by ruminants contributes to 30% of global livestock greenhouse gas (GHG) emissions (FAO, 2018), making ruminants one of the largest contributors per unit of feed intake. Dairy production has been cited as a major GHG emitter contributing to climate change, however increasing the milk yield (MY) per cow has been successful in increasing feed efficiency (FE) and reducing enteric GHG emissions per litre of milk production. This is essential in maintaining global warming < 1.5°C up to 2030 and net zero by 2050, however the potential associated decline in pregnancy rate (PR) and infertility is a main factor that may contribute to GHG emissions, mainly due to the decline in the length of productive life of dairy cows. Survey data and modelling has been used to evaluate carbon emissions (CO2-eq.) per day of calving interval (CI) greater than 365 d and per percentage increase in dairy herd replacement rate (RR). This thesis aims to to evaluate the postpartum ovarian activity to classify dairy cows that had typical and atypical ovarian cycle length and evaluate the fertility and production data and calculate the impact of the length of the CI and RR on CO2-eq. of dairy production from Holstein Friesian (HF) dairy cows. The thesis presents four experiments (Expt. 1 to 4) that evaluate the occurrence of atypical postpartum ovarian cycle length (ACL) and compare the effect of ACL with typical cycle length (TCL) on fertility using milk progesterone (P4) concentrations to assess postpartum (pp) ovarian cycles. This thesis compares the effect of ACL on the pp interval (PPI) to conception, CI and PR and RR, and apply previous UK estimates of CO2-eq. for each addition day over a CI of 365 d and additional percent of RR to compare the effect of ACL and TCL on CO2-eq. in relation to CI, RR, infertility and FE.